Comparison of the Effects of Local and Systemic Zoledronic Acid Application on Mandibular Distraction Osteogenesis - Dundar, Serkan; Artas, Gokhan; Acikan, Izzet; Yaman, Ferhan; Kirtay, Mustafa; Ozupek, Muhammed Fatih; Kom, Mustafa (Lippincott Williams & Wilkins, 2017)
Bisphosphonates are antibone resorptive drugs that are used to prevent bone tissue resorption in several skeletal diseases. The aim of this study was to examine the effects of systemic and local applications of zoledronic acid (ZA) on newly regenerated bone in a model of experimental distraction osteogenesis (DO). To do this mandibular DO was applied to 30 adult female Sprague Dawley rats, which were randomly divided into 3 groups: control, DO only, systemic zoledronic acid (SZA), and local zoledronic acid (LZA). In the LZA group, the gap between the bone fragments was filled with a gelatin sponge soaked in 2mg of ZA and 0.1 mL of sterile saline. In the SZA group, a single dose of 0.1 mg/kg ZA was administered systemically. After the surgery, there was a 5-day latent waiting period and 10-day distraction phase. Following a 28-day consolidation period, the rats were euthanized and theirmandibles were collected. The distracted bone area was seen to be filled with newly regenerated bone tissue in all 3 groups, both histologically and histomorphometrically. In addition, amounts of new bone formation, osteoblast cella, osteoclast (OC) cells, osteopontin, and vascular endothelial growth factor in the SZA and LZA groups were found to be higher when compared with the controls. Furthermore, in the SZA group, new bone formation, osteoblast, OC, osteopontin, and vascular endothelial growth factor were detected in significant amounts compared with the LZA group. Osteoclast numbers did not differ in a statistically significant manner in the SZA group with respect to the LZA group. Based on the results of this study, systemic and local applications of ZA could increase the formation of new bone in patients of DO, and systemic application is a more effective method compared with local application.
Keywords: Distraction osteogenesis; histomorphometry; new bone formation immunohistochemistry; zoledronic acid